Macunaíma 89. - Instituto Nacional de Artes Plásticas, Rio de Janeiro; Galerias Sérgio Milliet, Rio de Janeiro; Espaço Alternativo Rodrigo Mello Franco de Andrade, Rio de Janeiro; Macunaíma 1989, Rio de Janeiro (Rio de Janeiro : FUNARTE/Fundação Nacional de Arte, 1989)
Dacosta, Alexandre ; Lescher, Artur ; Stambowsky, Ernesto ; Cardoso, Fábio ; Moraes, Nina ; Vinci, Laura ; Andery, Felipe ; Lincoln ; Ribeiro, Flávia ; Fidelis, Gaudéncio ; Waetge, Gisela ; Lagoeiro, José Augusto ; Spaniol, José ; André, Marcus ; Dalio, Osmar ; Monteiro, Paulo ; Schmidt, Paulo ; Cardoso, Rodrigo ; Tassinari, Renata ; Sister, Sérgio ; Geisel, Lorena ; Homen, Ricardo
Macunaíma 89, FUNARTE/Instituto Nacional de Artes Plásticas, Rio de Janeiro ; Galerias Sérgio Milliet ; Espaço Alternativo Rodrigo Mello Franco de Andrade, Rio de Janeiro, 17 de maio a 7 de junho de 1989
kunstcatalogus